Political English : language and the decay of politics - Docherty, Thomas, 1955- (Bloomsbury Academic, 2019)
"From post-truth politics to 'no-platforming' on university campuses, the English language has been both a potent weapon and a crucial battlefield for our divided politics. In this important and wide-ranging intervention, Thomas Docherty explores the politics of the English language, its implication in the dynamics of political power and the spaces it offers for dissent and resistance. From the authorised English of the King James Bible to the colonial project of University English Studies, this book develops a powerful history for contemporary debates about propaganda, free speech and truth-telling in our politics. Taking examples from the US, UK and beyond - from debates about the Second Amendment and free-speech on campus, to the Iraq War and the Grenfell Tower fire - this book is a powerful and polemical return to Orwell's observation that a degraded political language is intimately connected to an equally degraded political culture."--Bloomsbury Publishing
Keywords: Language and languages -- Political aspects.; English language -- Political aspects.; Communication in politics.; Langage et langues -- Aspect politique.; Communication politique.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Communication in politics; English language -- Political aspects; Language and languages -- Political aspects